An Experimental Study of Ground-Based Equipment Real Time Data Transfer Possibility by Using Cellular Networks - Brodņevs Deniss; Kutins Aleksandrs (Electrical, Control and Communication Engineering)
An expanding mobile cellular network data transfer service offers cheaper wireless solutions for various data transfer needs. This paper presents an experimental testing of data transfer performance in 3G and 4G modes. The purpose of testing was to check the possibility of real-time and critical data transfer over the mobile cellular networks. The testing was performed in Riga in July and August 2016 using the most popular mobile service operators in Latvia: Tele2-LV, BITE-LV and LMT. The testing confirmed that the overload of Riga’s 4G networks causes serious service deterioration or even interruption. Riga’s 3G networks are more stable. However, 3G network service quality depends on a cell load. Lightly loaded 3G network meets real-time data transfer requirements of 100 ms one-way delay of the small packet traffic.